Electronic structure of the parent compound of superconducting infinite-layer nickelates - Hepting, M.; Li, D.; Jia, C. J.; Lu, H.; Paris, E.; Tseng, Y.; Feng, X.; Osada, M.; Been, E.; Hikita, Y.; Chuang, Y.-D.; Hussain, Z.; et al. (Nature materials, 2020)
The search continues for nickel oxide-based materials with electronic properties similar to cuprate high-temperature superconductors 1 – 10 . The recent discovery of superconductivity in the doped infinite-layer nickelate NdNiO 2 (refs. 11 , 12 ) has strengthened these efforts. Here, we use X-ray spectroscopy and density functional theory to show that the electronic structure of LaNiO 2 and NdNiO 2 , while similar to the cuprates, includes significant distinctions. Unlike cuprates, the rare-earth spacer layer in the infinite-layer nickelate supports a weakly interacting three-dimensional 5 d metallic state, which hybridizes with a quasi-two-dimensional, strongly correlated state with 3 d x 2 − y 2 symmetry in the NiO 2 layers. Thus, the infinite-layer nickelate can be regarded as a sibling of the rare-earth intermetallics 13 – 15 , which are well known for heavy fermion behaviour, where the NiO 2 correlated layers play an analogous role to the 4 f states in rare-earth heavy fermion compounds. This Kondo- or Anderson-lattice-like ‘oxide-intermetallic’ replaces the Mott insulator as the reference state from which superconductivity emerges upon doping. X-ray spectroscopy and density functional theory are used to show that the electronic structure of the parent compound of superconducting infinite-layer nickelates, while similar to the copper-based high-temperature superconductors, has significant differences.